Firm Specific Attributes and Stock Returns: A Case of Nepalese Insurance Companies - Shrestha, Purna Man (Nepalese Journal of Management Science and Research, 2019)
This paper empirically evaluates the explanatory power of the firm specific attributes such as size [Ln(ME], book-to-market equity [Ln(BE/ME)], and net worth per share [Ln(NWPS), on stock return (Rj) of Nepalese insurance companies listed in Nepal Stock Exchange (NEPSE). The study coverers the period of 2000/01 to 2017/18 with 12 insurance companies out of 22 listed insurance companies in NEPSE (Mid-July, 2018). The empirical analysis of this study concludes that, size [Ln(ME], book-to-market equity [Ln(BE/ME)] and net worth per share [Ln(NWPS) have explanatory power to explain the cross-section of stock return of Nepalese insurance companies. Among these variables book-to-market equity [Ln(BE/ME)] has strong explanatory power than other variables.